92 Strict – simulated tricky trips; a simulation based transfer course. (17th November 2016) - Sen, S; Shah, N; Bossy, M; Savine, R; Doyle, J; Lomax, S; Morrison, B; Somasundaram, K; MacGregor, M; Wright, J; McGearey, W; Pasquier, B; et al.
Abstract : Background: There are an estimated 11, 000 transfers that occur throughout the UK per year. 1 These are costly and dangerous and result in a three day increase in length of stay for critically unwell patients. 2 Due to the centralization of services and increase of tertiary centres these transfers are becoming more common. The original didactic "Tricky Trips course", initiated by SECCCN, required improvements based on candidate feedback. Due to significant variation in delivery and dwindling faculty numbers, the course needed modernising. There are well defined guidelines for transfer by the AAGBI and the ICS. With the development of a specialised simulation ambulance, an opportunity arose to develop a inter-professional simulation based transfer course. Description of innovation: The course format involves: Pre-course reading material Introductory workshop Faculty demonstration In course MCQ paper Simulated scenario based sessions "Problems on transfer" discussion session Candidates are assigned to inter-professional groups involving doctors, ODPs and nurses. Example simulated scenarios include: Packaging of the time-critical head injury CT Scan Level 3 Intra-hospital transfer Inter-hospital transfer including simulation ambulance drive Each session concludes with a faculty facilitated debrief session on technical and human factors aspects of transfers. Outcomes: Feedback has been excellent with 100% of candidates recommending this course. Feedback praise has been positive for scenario design, realism and organisation of the course. The course has attracted a HEKSS funding bid for development and is awaiting formal endorsement from the ICS. Take home messages: The STricT course has developed a standardised, curriculum mapped, interprofessional, simulated transfer training course. Giving candidates hands-on transfer and road ambulance training, learning outcomes are successfully achieved, producing more confident transfer teams. Developments for the future: Expanding scenario and MCQ bank Creating demonstration videos Offering the course package to other providers Reference: The Intensive Care Society (3rd Edition 2011). Guidelines for the Transport for the Critically Ill Adult 2 NW Knudsen et al . Impact of Interhospital Intensive Care Unit Transfers. Critical Care 2001;5 (Suppl 1);173. ICS - Intensive Care Society SECCCN - South East Coast Critical Care Network AAGBI - Association of Anaesthetists of Great Britain and Ireland